Digital transformation and moving towards developing smart libraries: Academic research and intellectual property rights - Edited by Keshava...at.el. (New Delhi D. P. S. Publishing, 2022)
About Digital transformation , Developing smart libraries, Academic research and intellectual property rights.
Keywords: Digital Library; Smart Library